Ideal Concept of Goods/Services Procurement Regulation for Pandemic Emergency Situations - Pracaya, Nikodemus; Puluhulawa, Fenty U (Damhil Law Journal, 2024)
The purpose of this article is to find corrective material for regulating the procurement of goods and services in an emergency / pandemic. The research method used in this research is the normative research method by taking a statute approach and a case approach. The results of this study indicate that there are serious challenges in complying with laws and regulations related to handling the Covid-19 Pandemic in 2020. Where the BPK finding number is the tip of the iceberg phenomenon of irregularities that may be committed by local governments. Where most of the local governments are not equipped with adequate evidence of price reasonableness. Therefore, the price of goods must be based on adequate price reasonableness documents, but most of the appointed goods and services providers do not have/will not submit evidence of adequate price reasonableness. This raises suspicions about whether the high price disparity is really a real economic phenomenon or just a fabrication by individuals trying to take advantage of the situation. In addition, there is an obligation from the Internal Auditor to conduct an audit of price reasonableness, but it was not carried out. In addition, BPK as an external auditor was also unable to conduct a maximum inspection due to constraints with the Health protocol and online audit system. This makes the opportunity or potential irregularities in financial management large and even undetectable.